(untitled) (Research, Society and Development, 2023)
The COVID-19 pandemic was declared on March 11, 2020 by the WHO, causing the world to enter into quarantine, measures such as the use of electronic devices, distance learning and virtual meetings were used to maintain social interaction. The study aimed to identify the relationship between the onset and progression of myopia in medical students at a private university in the state of Alagoas during the pandemic, compare the time spent using screens and the time spent in outdoor activities, and recognize strategies for managing and delaying the evolution of the pathology under study. This is a quantitative, exploratory and cross-sectional study, with the application of a questionnaire to university students. 108 students participated, among them, 61% already had a diagnosis of myopia (66/108) and about 36.1% of the interviewees spent between 9 and 12 hours on digital devices during the quarantine. Of the students diagnosed with myopia prior to the pandemic, 59.1% had an increase in the degree after performing the refractive exam carried out at the end of the pandemic. It was evident that the exacerbated stimulus of vision caused by the use of electronics and the low outdoor activity contributed to the refractive change of those who already had the diagnosis of myopia. However, although exposure to devices such as cell phones and televisions is already defined as harmful to vision, for those who were not myopic, this cause and effect relationship is not well ascertained, requiring further studies to prove it.